Balancing of lipid, protein, and carbohydrate intake in a predatory beetle following hibernation, and consequences for lipid restoration. (May 2016) - Noreika, Norbertas; Madsen, Natalia E.L.; Jensen, Kim; Toft, Søren
Graphical abstract: Highlights: Predatory beetles ( Anchomenus dorsalis ) regulated nutrient intake upon hibernation. Lipids and carbohydrates were used as interchangeable non-protein energy sources. Beetles regulated their intake towards similar net protein vs. non-protein energy. Similar amounts of lipid were deposited regardless of specific macronutrient intake. This obligate predator can actively exploit carbohydrates to balance energy budgets. Abstract: Carnivorous animals are known to balance their consumption of lipid and protein, and recent studies indicate that some mammalian carnivores also regulate their intake of carbohydrate. We investigated macronutrient balancing and lipid restoration following hibernation in the ground beetle Anchomenus dorsalis, hypothesizing that carbohydrates might be important energy sources upon hibernation when predator lipid stores are exhausted and prey are equally lean. We recorded the consumption of lipid, protein, and carbohydrate over nine days following hibernation, as the beetles foraged to refill their lipid stores. Each beetle was given the opportunity to regulate consumption from two semi-artificial foods differing in the proportion of two of the three macronutrients, while the third macronutrient was kept constant. When analyzing consumption of the three macronutrients on an energetic basis, it became apparent that the beetles regulated lipid and carbohydrate energy interchangeably and balanced the combined energy intake from the two macronutrients against protein intake. Restoration of lipid stores was independent of the availability of any specific macronutrient. However, the energetic consumption required to refill lipid stores was higher when a low proportion of lipids was ingested, suggesting that lipids were readily converted into lipid stores while there were energetic costs associated with converting carbohydrate and protein into stored lipids. Our experiment demonstrates that carbohydrates are consumed and regulated as a non-protein energy source by A. dorsalis despite an expectedly low occurrence of carbohydrates in their natural diet. Perhaps carbohydrates are in fact an overlooked supplementary energy source in the diet of carnivorous arthropods.